MOBILE RESPONSIVE USER INTERFACE DESIGN IN INFORMATION SYSTEMS DATA GROUPING RESIDENTS OF KLAMBIR LIMA KEBUN - Putra, Randi Rian; Putra, Eka (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
Kelurahan is the division of administrative regions in Indonesia under sub-districts. The sub-district is led by a lurah with the status of a Civil Servant. Kelurahan Pahlawan is a government agency that handles all population data. To be able to improve the grouping of citizen data and its reports to a higher agency, namely the district, steps are needed to develop a data grouping information system. The information system for grouping data on the residents of the village of Klambir Lima Kebun is a system that was built based on a user interface design with a responsive mobile system that was tested based on usability with the human centered design method. Human centered design is an approach method in the development and design of a user-focused system according to aspects of the needs and habits of the user. In the village of Klambir Lima Kebun, all information about the population has not been worked out optimally and there is no program to support work in the office. Office employees have difficulty grouping population data, still using the manual method or still in paper form. With the design of this system, it can help village officials in carrying out the process of grouping citizen data and speeding up service to the community as well as providing more effective and accurate information.